Sexuality and adolescence: basic education teachers' concepts - Maira Scaratti; Pâmela Roberta Rocha da Silva; Elisangela Argenta Zanatta; Maria Luiza Bevilaqua Brum (Universidade Federal de Santa Maria, 2016)
Aim: To know basic education teachers' notions about sexuality; to highlight strategies used to approach the issue sexuality and to investigate the importance of nurses' performance in school. Method: qualitative research conducted in 2014, with 47 teachers, through semi-structured interviews. Data were cathegorized through thematic analysis. Results: teachers consider sexuality as an integrating part of the human being, considering that it is influenced by social groups, family and media. They use various strategies to develop the theme sexuality such as technological resources, box of questions and texts. Also, they consider important the inclusion of nurses in school, since they act as a mediators in the discussions, helping adolescents and teachers. Conclusions: The study revealed that the theme sexuality needs to be widely discussed, especially among nurses and teachers in order to improve the applicability of new teaching methodologies and approaches on sexuality, with adolescents